Update of Giancarlo De Carlo’s participatory method: a case of experimentation - Barbara Bonanno (Techne)
The essay explores an updated application of Giancarlo De Carlo’s participatory method through the renovation of a hotel timeshare in Gioiosa Marea (ME), which was used by one hundred and thirty-five families. The experience integrated sociological enquiry, metric-environmental surveys, and subjective and objective tools to meet the needs of users who wished to adapt the spaces to their new living requirements. The shared design produced flexible solutions, improving functionality and comfort, and renewing the link between space and people. The experimentation allowed clients to re-evaluate the architect’s role as a social and cultural mediator in the development of living space, and the designer to develop a replicable method.